Design, fabrication and testing of hydro turbine with composite path runner for ultra-low head application - Chaulagain, Raj Kumar; Pokhrel, Dhiraj; Gautam, Kaurab; Khanal, Nabin; Bhatt, Harish (Journal of Innovations in Engineering Education, 2019)
This paper is focused on design a turbine with composite path runner for ultra low head application and finally analyze its performance under different test conditions. Literature review was the starting point of research and detailed design parameters for the turbine dimensions and materials were selected taking feasibility of fabrication and testing in hand. The testing was proposed on real site of Bagmati river at Kupandole, Lalitpur, Nepal where the turbine was subjected to fuse reeflowing water from the head of 1.3m and flowrate of 78 LPS that taken as site parameter. The 3D model for the turbine was developed in CATIA. For turbine height of 0.77m and runner minor diameter of 0.152m, simulations were carried out to find the most feasible number of blades, blade width, blade spacing, number of guide vanes and guide vane spacing using ANSYS simulation. Among the simulation the best arrangement was blade radial width of 62 mm, blade spacing of 54mm, guide vane spacing of 36.5 mm, total number of blades 25 and total number of guide vanes 7 keeping output power in mind. The experimental results were then compared with the data obtained from calculations and simulations. Turbine at part load of Qo/Qmax = 0.67 was tested and the resulting maximum efficiency was 21.1% at 87 RPM with available flow rate of 52 LPS.